Analisi Kinerja dengan Pendekatan Balanced Scorecard Pada PDAM Tirta Sakti Kabupaten Kerinci - Maryanto Maryanto (Akuntansi & Ekonomika, 2018)
Purpose of research this is to of performance PDAM Tirta Miraculous sub-province Kerinci with use the method Balanced Scorecard, writer do the research PDAM Tirta Miraculous sub-province Kerinci with take the data from year 2015 until year 2017 to analysis the in perpective. From result which have do to know that performance PDAM Tirta Miraculous sub-province Kerinci in general good enough, [the] mentioned ditunjukan with result analysis from masing masing in perpective. Pursuant to result research the can pulled conclusion that Balanced Scorecard represent the measurement method performance of which very good use because Balanced Scorecard mengankat aspek-aspek important which disregard by measurement in traditional. Result of measurement the accurate will gave picture of decision the good to the management in the case of planning, decision making to realize a[n vision and mission the organizational.